2019
DOI: 10.1109/tcsii.2018.2873635
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration of Implication Logic Based on Volatile (Diffusive) Memristors

Abstract: Implication logic gates that are based on volatile memristors are demonstrated experimentally with the use of relay-based volatile memristor emulators of an original design. The fabricated logic circuit involves two volatile memristors and it is capable of performing four fundamental logic functions (two types of material implication and the negations thereof). Moreover, current-voltage characteristics of individual emulators are recorded and self-sustained oscillations in a resistor-volatile memristor circuit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The device returns to its original insulating state when the field is removed with a characteristic relaxation time (replicating the refractive period of neurons). That required additional short memory may come from the relaxation time of some volatile resistive switching phenomena [738] , [739] . Pickett et al [740] demonstrated that the Na gain, and the refractory period (Fig 11(a)).…”
Section: Neuristorsmentioning
confidence: 99%
“…The device returns to its original insulating state when the field is removed with a characteristic relaxation time (replicating the refractive period of neurons). That required additional short memory may come from the relaxation time of some volatile resistive switching phenomena [738] , [739] . Pickett et al [740] demonstrated that the Na gain, and the refractory period (Fig 11(a)).…”
Section: Neuristorsmentioning
confidence: 99%
“…For unipolar switching, Joule heating plays the most dominant role. Unipolar as well as bipolar resistive switching has been observed in TiO 2 thin films, ,, whereas nanostructures show mostly bipolar switching. , However, in neuroscience, memristors have been found to be a great candidate for emulating synaptic functions, where the synaptic weight is equivalent to the conductance change. A short- and long-term plasticity enables learning and memory of the bioinspired neuromorphic system. The TiO 2 nanorod arrays (NRAs) we present show short- and long-term memory states, which are dependent on the hydrothermal growth (HG) temperature. HG itself has been investigated in detail previously. , It has been shown that the growth on a fluorine-doped tin oxide (FTO) results in a perpendicular growth of TiO 2 nanowires, which contain a finger-like structure at the upper part of the nanowire, as well as a V-shaped defect cascade from the top to the bottom of the nanowire. , The individual fingers are single-crystalline TiO 2 rods, adjacent to one another and shifted relatively by half of the lattice plane .…”
Section: Introductionmentioning
confidence: 99%
“…Their small size and low power consumption [7] make them perfect for various fields, including computer memory [8], encrypted communication [9,10], neural networks [11], etc. Nowadays, many types of a physical device implementation are under investigation [12,13,14,15,16,17]. Memristor is a two-terminal device, and its resistance (memristance) depends, in general, on some internal parameter, which can be controlled by total current (or charge) flowing through it, making a memristor similar to a biological synapse or neuron.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, socalled nonvolatile, passive memristors [18] offer an electronic analog to biological synapses. A complementary device, the volatile memristor [16], can be used to construct an electronic equivalent of biological neurons. Such an artificial neuron, comprising of a memristor, capacitor, and a resistor, is locally active within a hysteretic negative differential resistance regime in the memristive current-voltage characteristic.…”
Section: Introductionmentioning
confidence: 99%